PENGARUH PENAMBAHAN SERBUK BENTONIT PADA CAMPURAN BETON TERHADAP KUAT TEKAN BETON - Hamsyah Hamsyah; Jumardi Safri (Universitas Muhammadiyah Enrekang, 2020)
This research purposed to analyzing the bentonite powder with the mixture concrete for the strength of concrete K 225 and evaluating the comparison bentonite powder to concrete mixture concerning the compressive strength of concrete K 225. With development the concrete construction in this country Indonesia,so this reseach more leads to quality improvement concrete by using added bentonite materials. From the reseach results can be drawn a conclusion that is the addition of bentonite on concrete mixture will increase the compressive strength of concrete the highest strength value that achieved for the concrete with bentonite degrees 10 %, with average results as amount 22,175 Mpa. And then, bentonite degree 25 % and 50 %. The concrete become decreased compressive strength of concrete as amount 16.301 and 9,979 Mpa. Compressive strength of concrete with added bentonite degree as amount 10 %, 25 % and 50 % with average compressive strength amount 22,175 Mpa, 16,301 Mpa and 9,979 Mpa not reached the standard specification quality of concrete K225.